Best Practices for Promoting Teachers’ Professional Development in Malaysia - Mohamad Johdi Salleh; Muhammad Hatta (UMT Education Review, 2019)
Cluster schools in Malaysia were formed to employ best teachers to achieve educational outcomes corresponding to the 4th industrial revolution (IR). This study examines the best practices of promoting teachers’ professional development prevalent among principals of cluster secondary schools in Malaysia. The Principal Instructional Management Rating Scale (PIMRS) was used as the data collection instrument. A diverse sample of 871 respondents belonging to both genders, different ethnicities and types of schools, and having various designations at schools was drawn randomly using cluster sampling. The researcher employed descriptive statistical procedures involving frequency count and percentage distribution as the means to analyze the collected data. The use of such data is a standard practice in Malaysia which is employed to plan professional development among principals of cluster secondary schools. The study indicated that the best practice of developing teacher professionalism among principals of cluster secondary schools in Malaysia according to principals’ and teachers’ perceptions was ‘setting aside time at faculty meetings for teachers to share ideas about instruction or information from in-service activities.’ The findings will effectively assist the process of promoting a positive school learning climate among the principals and teachers of secondary schools in Malaysia in the wake of meeting the goals of National Philosophy of Education, Vision 2020 and the aspirations of the Malaysia Education Development Plan 2013-2025 in the era of IR 4. Other school principals may use the outcomes of this research to facilitate and improve students’ academic performance in their respective schools and join hands in the collective effort of raising the work force capable of meeting national goals at par with international standards.